PELATIHAN DASAR DETEKSI DINI PERTUMBUHAN DAN PERKEMBANGAN ANAK BAGI GURU RA AL-IKHWAN BANGKALAN - Selvia Nurul Qomari; Enggal Sari Maduratna; Nailufar Firdaus (STIKES NGUDIA HUSADA MADURA, 2020)
The growth and development of children has increased rapidly at an early age, from 0 to 5 years. This period is often referred to as the